Experimental investigation of scouring around a single spur under clear water conditions. Issue 3 (16th November 2021) - Özyaman, Cansu; Yerdelen, Cahit; Eris, Ebru; Daneshfaraz, Rasoul
Abstract: This study presents the effect of different parameters on the scouring process around spur dikes. Our research group's stated objective was to evaluate the effects of sediment gradation, flow depth, spur angle and spur length on the scouring process. Since most existing studies generally employed uniform sediment, in this study uniform and non-uniform sediment were selected. Experiments were made in a rectangular open channel in uniform flow conditions. Results showed that the effect of the spur dike length and the orientation angle on sediment scour varies with the type of sediment used. Scour volumes were 40% greater in uniform sediments than in non-uniform sediments. Measured scour depth was maximum at spurs perpendicular to the flow, whereas the scour volume was maximum at spurs directed upstream. The scour depth increased with an increase in the spur length; however, the effect of spur length on scouring varied at a contraction rate of 0.29 for uniform sediments and 0.36 for non-uniform sediments. A multiple regression analysis was also performed, and four equations were suggested to predict the scour depth and scour volume. Comparisons were made with the literature equations applicable for clear-water scouring to check the suggested equation. Because of the wide range of contraction ratios considered in this study, the equations which considered the contraction effect yielded better estimates. HIGHLIGHTS: In this study in addition to scour depth measurements, we made scour volume measurements and drew contour line maps to observe the scouring area. Since the sediments in rivers and natural channels are non-uniform, we performed the experiments with both uniform and non-uniform sediments. Based on the experimental results, we propose four different equations to quantify the scour depth and scour volume in uniform and non-uniform sediments.